Pengaruh Sosial Ekonomi terhadap Kualitas Rumah di Kelurahan Aur dan Kelurahan Hamdan - Mbina Pinem (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2015)
This research aims to know household’s social and economic effect to quality of houses, people in Subdistrict of Aur and Hamdan, Medan Maimun District, City of Medan. the population in this research is entire of household of the slums settlement in the area, as amount 70 householders of sample. Collecting data was conducted by observation and filling questionaire by respondents. The result of research shows that class of social and economic wealth of people (income) effect to quality of house.